DNA repair capacity after γ-irradiation and expression profiles of DNA repair genes in resting and proliferating human peripheral blood lymphocytes - Mayer, Claudia; Popanda, Odilia; Bartsch, Helmut; Schmezer, Peter (DNA repair, 2002)
DNA repair plays an important role in maintaining genomic integrity, and deficiencies in repair function are known to promote cancer development. Several studies have used the individual capacity to repair DNA damage in peripheral blood lymphocytes (PBLs) as a cancer risk marker. As the cell’s ability to remove DNA damage may be correlated with proliferative activity, it is an important question whether quiescent or dividing cells should be used in such studies. The aim of our study was to compare DNA repair capacity and expression profiles of 70 known DNA repair genes, both in resting and phytohemagglutinin (PHA) stimulated human PBLs. Using the comet assay, γ-radiation-induced DNA damage and repair in lymphocytes was analyzed. No difference, neither in the rate of radiation-induced DNA damage nor in DNA repair capacity between PHA-stimulated and non-stimulated PBLs was observed. Stimulated cells, however, showed significantly elevated values for background damage. Transcriptional profiles of repair genes were analyzed using cDNA arrays. Hybridization experiments were performed with mRNA isolated from both unstimulated and PHA-stimulated PBLs. More than 70% of all evaluated genes had constant expression levels. Twelve genes responded with a more than two-fold increase of transcripts to the mitogenic stimulus. Most of the up-regulated repair enzymes are also known to play a role in DNA replication. In conclusion, the data presented here suggest that all repair proteins needed for the repair of γ-irradiation induced DNA-damage, that can be detected by the alkaline comet assay, are already present in G0 cells at sufficient amounts and do not need to be induced once lymphocytes are stimulated to start cycling. Our results thus do not support a general increase in DNA repair activity of PBLs by PHA stimulation, and the use of stimulated PBLs in molecular epidemiological studies on DNA repair of γ-irradiation induced DNA damage seems not to be mandatory.